Hubungan Karakteristik Individu Dengan Perilaku Menggunakan Masker Sebagai Upaya Pencegahan COVID-19 Pada Dewasa Muda di Kota Pekanbaru - Tyagita Widya Sari; Nike Elpita (LPPM Universitas Abdurrab, 2023)
Coronavirus Disease 2019 (COVID-19) is a disease that has never been previously identified in humans. The case is increasingly acclaimed on a daily basis around the world, including in Indonesia. At the Riau Province level, 31,397 confirmed cases of COVID-19 have been reported from 12 districts/cities on February 28, 2021 and the Pekanbaru city is the most abundant COVID-19 case report in the Riau province. Due to the continued increase in the incidence of COVID-19, the Indonesian government adopted a policy to socialize the mask wearing behavior to reduce and break the chain of transmission of COVID-19. However, there are still many people in Indonesia who do not wear masks. Most of Pekanbaru's people who often violate health protocols are dominated by young adults, namely those aged 18-25 years, where they have various reasons for not wearing masks. The objective of this study was to determine the correlation of individual characteristics and mask wearing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021. This research used an analytic observational with a cross sectional study design. This research was conducted on a population of young adults in Pekanbaru City on June 2021. The sampling technique was carried out by cluster sampling with a sample size of 440 respondents. Data analysis was conducted through chi square's test and spearman's correlation test for p-value and coefficient correlation (r). There were no significant correlation between gender variable (p-value 0,436), education level variable (p-value 0,538), and employment status variable (p-value 1,000) and mask wearing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021. The individual characteristics (gender, education level, and employment status) have no correlation with mask wearing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021.